The United Nations system for global development: political and economic agenda (Comillas Journal of International Relations, 2015)
Since its foundation, the United Nations Organization has created and implemented a series of public policies, indicators and programs that promote sustainable development. Political leaders all over the world – in both developed and developing countries – have supported the fulfilment of these goals, which have shaped the development agenda of the UN within the framework of the Millennium Development Goals (MDGs). The MDGs aim at improving living standards around the globe through the establishment of a sustainable economic system in the social, economic and environmental domains. The World Bank (WB) and the International Monetary Fund (IMF) have been key institutions when it comes to issuing public policy recommendations for the attainment of the MDGs. This article will first analyze the role of these institutions and macroeconomic policies and then suggest a set of supplementary meso and microeconomic policies that, according to the author, could enhance the potential for macroeconomic policies to achieve a sustainable development and fulfill the Millennium Development Goals.
Keywords: United Nations; development; sustainable competitiveness; economic policy